2018
DOI: 10.4103/jnrp.jnrp_62_18
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Spectral Severity of Alcoholism on Visual-Evoked Potentials: A Neuropsychiatric Perspective

Abstract: Background:The deleterious effects of alcohol on the brain are replete in literature. Only a few neurophysiologic measures can pick up the neuronal dysfunctions, one of them being visual-evoked potential (VEP). A very limited amount of data exists on the progression of neural abnormalities related to the spectral severity of alcoholism.Aim of the Study:To evaluate the impact of spectral severity of alcoholism through VEP and to understand the emergence of any specific pattern or morphometric abnormalities rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This suggests that individuals with SAUD may display alterations in the striate cortex, the dorsal extrastriate cortex of the middle occipital gyrus, or the ventral extrastriate cortex of the fusiform gyrus, all these areas being potential P1 generators (Di Russo et al., 2002, 2005; Holder et al., 2010). Delay and changes in the waveform of the N75 (C1) (Cosi et al., 1986; Devetag, 1988; Kelley et al., 1984) and the N145 (N1) (Devetag, 1988), of striate and extrastriate origin (Di Russo et al., 2002, 2005), respectively, have also been reported, whereas other studies did not reveal any change in pattern‐reversal VEP (Bauer & Easton, 1996; Emmerson et al., 1987; Kothari et al., 2018; Meinck et al., 1990). These discrepancies might be due to differences in medication (e.g., use of disulfiram in Kelley et al., 1984), length of abstinence (e.g., a few days/weeks in Cosi et al., 1986; 3 and 6 months in Bauer & Easton, 1996 and Kothari et al., 2018; more than 1 year in Devetag, 1988), or other experimental differences among which potential fluctuations in the locations, sizes, and reversal frequencies of the checkerboards (Holder et al., 2010).…”
Section: Temporal Characterization Of Visuoperception Through Electromentioning
confidence: 96%
“…This suggests that individuals with SAUD may display alterations in the striate cortex, the dorsal extrastriate cortex of the middle occipital gyrus, or the ventral extrastriate cortex of the fusiform gyrus, all these areas being potential P1 generators (Di Russo et al., 2002, 2005; Holder et al., 2010). Delay and changes in the waveform of the N75 (C1) (Cosi et al., 1986; Devetag, 1988; Kelley et al., 1984) and the N145 (N1) (Devetag, 1988), of striate and extrastriate origin (Di Russo et al., 2002, 2005), respectively, have also been reported, whereas other studies did not reveal any change in pattern‐reversal VEP (Bauer & Easton, 1996; Emmerson et al., 1987; Kothari et al., 2018; Meinck et al., 1990). These discrepancies might be due to differences in medication (e.g., use of disulfiram in Kelley et al., 1984), length of abstinence (e.g., a few days/weeks in Cosi et al., 1986; 3 and 6 months in Bauer & Easton, 1996 and Kothari et al., 2018; more than 1 year in Devetag, 1988), or other experimental differences among which potential fluctuations in the locations, sizes, and reversal frequencies of the checkerboards (Holder et al., 2010).…”
Section: Temporal Characterization Of Visuoperception Through Electromentioning
confidence: 96%
“…Marr et al [12] reviewed 114 consecutive children under 10 years of age with high hypermetropia (greater than + 5.00 DS) during a 5-year period and reported that high hyperopia has a similar incidence of associated ocular abnormalities as high myopia. [13] It's a widespread understanding that smoking and alcohol has an adverse effect on the cardiovascular system and the central nervous system. They also have damaging effects on visual cortex.…”
Section: Effect Of Refractive Errors (Re) On Vep Readingsmentioning
confidence: 99%